2005
DOI: 10.1002/mrm.20361
|View full text |Cite
|
Sign up to set email alerts
|

Spatial characterization of T1 and T2 relaxation times and the water apparent diffusion coefficient in rabbit Achilles tendon subjected to tensile loading

Abstract: Tendons exhibit viscoelastic mechanical behavior under tensile loading. The elasticity arises from the collagen chains that form fibrils, while the viscous response arises from the interaction of the water with the solid matrix. Therefore, an understanding of the behavior of water in response to the application of a load is crucial to the understanding of the origin of the viscous response. Three-dimensional MRI mapping of rabbit Achilles tendons was performed at 2.0 T to characterize the response of T 1 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
6
24
0
Order By: Relevance
“…Our results provide the first evidence that links acute changes in transverse morphology to corresponding changes in tendon length after exercise. Short-term changes in Achilles free tendon transverse morphology after exercise (Fahlstrom and Alfredson, 2010;Grigg et al, 2010Grigg et al, , 2009Grigg et al, , 2012Ooi et al, 2015;Wearing et al, 2011Wearing et al, , 2013Wearing et al, , 2008 may therefore be indicative of transient mechanical creep of the tendon (Lichtwark et al, 2013;Obst et al, 2015), whereby increased collagen fibril packing linked to longitudinal creep and reduction of collagen crimp could promote fluid redistribution within, and out of, the tendon (Grigg et al, 2009;Hannafin and Arnoczky, 1994;Wellen et al, 2005). It should be noted that although we did not detect any change in tendon volume at rest or during 70%…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Our results provide the first evidence that links acute changes in transverse morphology to corresponding changes in tendon length after exercise. Short-term changes in Achilles free tendon transverse morphology after exercise (Fahlstrom and Alfredson, 2010;Grigg et al, 2010Grigg et al, , 2009Grigg et al, , 2012Ooi et al, 2015;Wearing et al, 2011Wearing et al, , 2013Wearing et al, , 2008 may therefore be indicative of transient mechanical creep of the tendon (Lichtwark et al, 2013;Obst et al, 2015), whereby increased collagen fibril packing linked to longitudinal creep and reduction of collagen crimp could promote fluid redistribution within, and out of, the tendon (Grigg et al, 2009;Hannafin and Arnoczky, 1994;Wellen et al, 2005). It should be noted that although we did not detect any change in tendon volume at rest or during 70%…”
mentioning
confidence: 70%
“…These short-term reductions in AP diameter after exercise have been suggested to reflect fluid exudation from the tendon core to the peri-tendinous space as a result of the creation of positive hydrostatic pressure within the tendon when tendon fibres stretch and pack under tensile load (Grigg et al, 2009;Hannafin and Arnoczky, 1994). While in vitro studies demonstrate load-dependent changes in fluid content and tendon dimensions in response to repeated loading (Hannafin and Arnoczky, 1994;Helmer et al, 2006;Wellen et al, 2005), in vivo studies of the human Achilles tendon report mixed findings with respect to exercise-induced changes in tendon volume (Pingel et al, 2013a, b;Shalabi et al, 2004;Syha et al, 2013) and crosssectional area (CSA) (Burgess et al, 2009;Farris et al, 2012;Neves et al, 2014;Ooi et al, 2015); discrepancies that may reflect different exercise interventions, populations or imaging methods used to assess tendon morphology. It is also currently unclear whether changes in transverse morphology and strain following exercise are uniformly distributed across the length of the tendon, occur along the medio-lateral (ML) diameter, related to changes in longitudinal deformation, or are more pronounced under tensile load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that permeability is strain (Lai et al 1981;Weiss and Maakestad 2006;Yin and Elliott 2004), porosity (Chen et al 1998) and/or voids ratio (van der Voet 1997) dependent. Higher water content in the peripheral rim compared to the tendon core suggests that the porosity or voids ratio may also be depth dependent within a tendon (Wellen et al 2005). The permeability in tendon is also believed to be anisotropic with a higher permeability along the fiber direction than across the fibers Chen et al 1998;Han et al 2000).…”
Section: Tendon Permeabilitymentioning
confidence: 97%
“…23 The novelty of the work from Komlosh et al is that they experimentally demonstrated that the microscopic anisotropy of macroscopically isotropic sample, which is not accessible with conventional single direction PGSE method, can be detected at low q regime using double PGSE. Such techniques may be useful for studying porous media and biological tissues, such as tendons 24,25 and brain gray matter with potential clinical applications because of its sensitivity in the low q regime compatible with clinically available gradient strength. 23 …”
Section: B Multiple Diffusion Nmr Scattering Experimentsmentioning
confidence: 99%